Interpretation of 1H-NMR spectrum of alginate by 1H-1H TOCSY and COSY spectrum - Kinh, Chu Dinh; Thien, Tran Vinh; Hoa, Tran Thai; Khieu, Dinh Quang (Vietnam Journal of Chemistry, 2014)
The sodium alginate was prepared from brown seaweeds in Thua-Thien-Hue coastal area. The obtained alginate was characterized by 1H-NMR, 1H-1H TOCSY and COSY spectra. The assignment of alginate peaks in 1H-NMR spectrum is 5.09, 4.446, 4.152, 4.318, 4.135 ppm in correspondence to H1, H2, H3, H4, H5 of D-mannuronic acid and 5.473, 4.318, 4.446, 4.571, 4.883 ppm in correspondence to H1, H2, H3, H4, H5 of L-guluronic acid, respectively. The present results are essential for the investigating guidance of alginate and its derivatives.